The Right To Inquiry: Its Influence on The Results of The 2024 General Election - Muhtar Muhtar; Tri Setyo; Opniel Harsana B Pongkapadang; Iwan Henri Kusnadi; Diah Apriliani (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Based on the explanation above, it can be concluded that this research aims to analyze the function of the People's Representative Council's right to inquiry in influencing the results of the 2024 general election. In line with the characteristics and color of sentences that researchers use in this article, this research is qualitative research with a normative/normative approach. approach to regulations and laws relating to the era of the right to inquiry, the history of the right to inquiry, the scope of the right to inquiry, the object of the right to inquiry, and the influence of the right to inquiry on the results of the 2024 Presidential and Vice Presidential general elections. In line with qualitative research with other descriptive approaches, research This uses secondary data in the form of statutory regulations relating to the right to inquiry, legal books, scientific articles, and various other secondary legal sources which are usually used as references in qualitative research with a normative approach. These data were analyzed using the method of grammatical legal interpretation, namely interpreting word for word in statutory regulations, legal doctrine and scientific articles. As well as a systematic legal interpretation method in accordance with the hierarchy of laws and regulations.